Recognition of dominant attractants by key chemoreceptors mediates recruitment of plant growth‐promoting rhizobacteria - Feng, Haichao; Zhang, Nan; Fu, Ruixin; Liu, Yunpeng; Krell, Tino; Du, Wenbin; Shao, Jiahui; Shen, Qirong; Zhang, Ruifu (Environmental microbiology, 2019)
Summary Chemotaxis to plant root exudates is supposed to be a prerequisite for efficient root colonization by rhizobacteria. This is a highly multifactorial process since root exudates are complex compound mixtures of which components are recognized by different chemoreceptors. Little information is available as to the key components in root exudates and their receptors that drive colonization related chemotaxis. We present here the first global assessment of this issue using the plant growth‐promoting rhizobacterium (PGPR) Bacillus velezensis SQR9 (formerly B. amyloliquefaciens). This strain efficiently colonizes cucumber roots, and here, we show that chemotaxis to cucumber root exudates was essential in this process. We conducted chemotaxis assays using cucumber root exudates at different concentrations, individual exudate components as well as recomposed exudates, taking into account their concentrations detected in root exudates. Results indicated that two key chemoreceptors, McpA and McpC, were essential for root exudate chemotaxis and root colonization. Both receptors possess a broad ligand range and recognize most of the exudate key components identified (malic, fumaric, gluconic and glyceric acids, Lys, Ser, Ala and mannose). The remaining six chemoreceptors did not contribute to exudate chemotaxis. This study provides novel insight into the evolution of the chemotaxis system in rhizobacteria.